In-situ measurements of engine particulate filter ash deposits via X-ray computed tomography scanning. Issue 8 (22nd June 2021) - Wang, Yujun; Wang, Ben; Kamp, Carl J.; Rogoski, Leigh; Ryan, Connor; Cunningham, Michael J.
Abstract: Engine particulate filters have been widely applied for both compression and spark-ignition engines due to the stringent emission regulations across the world. The in-situ density of ash deposits is critical to the degradation of filter performance and cannot be readily measured by traditional methods. In the present study, a method of measuring the density of ash deposits across a filter is developed using an industrial X-ray computed tomography (CT) apparatus. An array of density references attached to the filter sample are utilized to establish the correlation between ash density and CT image grayscale, which then is applied to estimate the density of ash deposits in a filter. The CT results are in close agreement with the density data from the dedicated lab measurements, where the average differences are around 8%. The CT approach has been demonstrated as a nondestructive means to measure the ash deposits in the three-dimensional space, offering more efficient, accurate, and reliable results than the traditional approaches. Copyright © 2021 American Association for Aerosol Research